Mechanical and thermal characterization of resin-infused cotton fabric/epoxy composites: Influence of woven construction parameters and surface treatments - Owen M.M.; Wong L.S.; Achukwu E.O.; Romli A.Z.; Shuib S.B. (SAGE Publications Ltd, 2025)
This study explores the mechanical and thermal characterization of epoxy-based composites reinforced with chemically modified woven cotton fabrics using the resin infusion technique. The woven fabrics construction parameters were varied in terms of weft yarn counts (16, 20, and 24 Tex) and pick densities as defined by pick wheel teeth (PWT) (30, 36, and 41T). The fabrics were surface treated with 6% concentration of sodium hydroxide (NaOH) using the alkali treatment method. The obtained results revealed that mechanical strength improved with decreasing weft yarn count and increasing PWT. Notably, chemically treated composites with the highest PWT exhibited superior strength compared to untreated counterparts, attributed to more compact microstructures, reduced fabric/fiber breakages, and enhanced interfacial bonding between the reinforced plain-woven cotton fabric and epoxy matrix. Thermogravimetric analysis (TGA) showed that all composites have higher thermal stability above 300C, with untreated fabric composites exhibiting the highest resistance to degradation, whereas the treated composite quickly degraded at an onset temperature of 288.4C due to the removal of the hemicellulose, decomposition of the cellulose, and lignin content. In conclusion, the study indicates that surface treatment and woven construction parameters such as weft yarn counts and pick wheel teeth, as well as the resin infusion technique, significantly influence the mechanical, microstructural, and thermal properties of resin-infused woven cotton reinforced composites for potential application in industrial and automotive sectors, offering lightweight, durable solutions for components such as construction and building panels, doors, and roof panels. ? The Author(s) 2024.